MASYARAKAT HINDU DALAM POLITIK NKRI MENUJU MASYARAKAT SIPIL - I NENGAH DUIJA (Purwadita : Jurnal Agama dan Budaya, 2017)
Peoples Hinduism is one component of the whole Indonesian nation from a state (nation state). Therefore, the position and its position in the Republic of Indonesia is actually the same, but  in  the  context  of  national  politics  often  a  question  of  what  is  by  Antonio  Gramsci  as  a political regional hegemony. Hegemony is happening is the issue of access to power, economic, social, cultural,  religious, and even become  a "majority  versus minority".  They are  the social and  political  construction  that  is  too  dominant  countries  penetrated  the  realm  of  privacy  of citizens countries. Based on that idea, then in recent decades appears "penggugatan" against the domination of  the  country  by  the  growth  of  the  socalled  civil  society  (civil  society).  The  growth  of  civil society is determined by the movement of the middle class (midle class), the emergence of a propeople NGOs, the organic intellectual movement (to borrow a phrase Gramsci) and other social movements. In this regard, the Hindu community has a function in foster civic values ??able to forge the formation of civil society itself. These values ??are the basic power (spirit) the formation of civil society in Indonesia.